2020
DOI: 10.4314/sokjvs.v18i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of <i>Brucella</i> infection in small ruminants from two institutional farms and a slaughter slab in Zaria, Nigeria

Abstract: Brucellosis has continued to become a disease of major economic concern in developing countries. In a study to determine the seroprevalence of brucellosis in small ruminants in Zaria, Kaduna State, Nigeria, 1036 samples comprising 768 goats from institutional farms (n=384) and a slaughter slab (n=384), and 268 sheep all from institutional farms were used. The sera samples obtained from the animals were subjected to the Modified Rose Bengal Plate Test (m-RBPT) followed by Serum Agglutination Test with ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
2
12
5
Order By: Relevance
“…This is capable of spreading brucellosis, should the abortions be due to brucellosis. This agrees the study carried out by Kaltungo (2018) and Buhari (2019) who attributed the spread of brucellosis in flocks of sheep and goats in Sokoto and Kaduna State respectively to extensive management system of the flocks. Bale (1980) reported that the system of husbandry greatly influences the spread of brucellosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is capable of spreading brucellosis, should the abortions be due to brucellosis. This agrees the study carried out by Kaltungo (2018) and Buhari (2019) who attributed the spread of brucellosis in flocks of sheep and goats in Sokoto and Kaduna State respectively to extensive management system of the flocks. Bale (1980) reported that the system of husbandry greatly influences the spread of brucellosis.…”
Section: Discussionsupporting
confidence: 92%
“…Genetically, ten species of the genus Brucellahave been documented and they include B.abortus, B. melitensis, B. suis, B. ovis, B. canis, and B. neotome, B pinipedialis, B ceti, B muris and B inapinata. Of these Brucella abortus is the species of Brucella documented to cause brucellosis in horses (Kaltungo et al, 2013). Brucellosis has been reported in many animal species in Nigeria (Falade et al, 1975;Okoh et al, 1978;Falade and Shonekan, 1981;Adamu and Ajogi, 1995;et al, 2010;Ehiziboloet al, 2011;Ardo and Abubakar, 2016;Baba, 2016;Tijani et al, 2017;Kaltungo, 2018;Njoga et al, 2018;Ado, 2019;Baba, 2019;Buhari, 2019). These reports seem to indicate that brucellosis is endemic and problematic in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…It could also indicate a possible effect of drugs that the camels might have been treated within the efforts of the owners to deworm them against helminth parasites. Kaltungo (2018), Baba (2019) and Buhari et al (2020) all reported livestock owners treating their animals against various diseases, especially through the use of plants.…”
Section: Discussionmentioning
confidence: 99%
“…This clearly showed that they did not understand the implications of the nonuse of these facilities. Thus, they can acquire zoonotic diseases such as brucellosis as Baba [19] and Buhari [29] have shown that Brucella abortus, B. suis and B. ovis antigen can be harvested from the blood of apparently normal cattle, sheep, goats and horses.…”
Section: Discussionmentioning
confidence: 99%